Minimizing the Number of Spans for Terrestrial Fiber-Optic Systems Using Quasi-Single-Mode Transmission - Jian Zhao; Inwoong Kim; Olga Vassilieva; Tadashi Ikeuchi; Wei Wang; He Wen; Guifang Li (IEEE Photonics Journal)
We show that quasi-single-mode transmission in few-mode fibers (FMFs) can reduce the number of spans for a fixed transmission distance and, consequently, the cost per bit for terrestrial transmission systems by minimizing both the Capex and Opex. The Gaussian-noise model is employed to estimate the nonlinear noise power spectral density both, which depends on the effective area of the FMF and span length, for Er-doped fiber amplifier (EDFA) and hybrid Raman/EDFA systems. Together with amplified spontaneous emission noise, an optical signal-to-noise ratio (OSNR) for a fixed transmission distance as a function of the effective area of the FMF and span length can be obtained. Given a target OSNR for a particular modulation format, we determine the maximum span length or the minimum number of spans as the effective area of the FMF varies both analytically and through numerical simulations. The effect of multipath interference in the FMF on the minimum number of span has also been investigated.